The Underpants Zoo - Sendelbach, Brian (New York : Scholastic, 2011)
Invites the reader to visit a new zoo, where each of the animals sports underwear suited to his or her own personal style.
Accelerated Reader AR
Keywords: Stories in rhyme; Stories in rhyme; Zoos -- Juvenile fiction; Underwear -- Juvenile fiction; Zoo animals -- Juvenile fiction; Clothing and dress -- Juvenile fiction; Humorous stories